Hymnograpic evidence for the exchange of saints between Egypt and Syria in the first millenium - Anna Rogozhina (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article discusses a process that may be defi ned as an “exchange of saints” between Egypt and Syria in the second half of the fi rst millennium. Coptic synaxaria and liturgical books contain commemorations not only of the local martyrs who were born and suff ered in Egypt, but also a great number of commemorations of foreign saints who later became appropriated by the Coptic Church, such as a group of the so-called Antiochene saints whose relics were claimed to belong to Egypt, either because these saints were martyred in Egypt or because the relics had been transferred to Egypt at some point. The presence of these saints in early hymnographic collections, preserved in two manuscripts of the 9th century (M574 and M575 of the Pierpont Morgan Library), provides ample evidence of the continuing and lasting interest of the Egyptian Christians in Antiochene saints. Such enthusiasm could probably be explained by the work of Severus of Antioch (465‒538) who did much in order to promote the exchange of saints between the two communities. The article also examines the seeming absence of reciprocity on the Syrian side and reviews the evidence provided by the early material, such as the hymns attributed to Severus of Antioch, which came down to us in Syriac translation revised by James of Edessa in the 7th century. One of these texts, a hymn dedicated to the Egyptian martyrs, is of particular interest with regard to the “exchange of saints” and shows that the process was in fact reciprocal.